Fiber Bragg grating in-situ detection method for curing characteristics of GIS epoxy/Al2O3 composite insulation materials - Yingying Zhang; Yanpeng Hao; Zikui Shen; Dongyuan Du; Hongru Mi (Polymer Testing)
Excessive residual strain generated by curing shrinkage of epoxy/Al2O3 composite insulation materials can reduce the mechanical properties of gas-insulated metal-enclosed switchgear (GIS) insulators. The process and formula optimization of insulators lack effective detection methods. A thermocouple-compensated fiber Bragg grating in-situ detection method for seven high-temperature curing characteristics is proposed. The curing shrinkage characteristics and residual strain generation mechanism of this material cured at 114 °C are studied. The cured residual strain is calculated by the total central wavelength shift of the grating and the thermocouple temperature change inside the sample at the end of the curing process. The curing degree, curing initiation time, and curing completion time are calculated by the temperature inside the sample and the surface temperature of the mold based on the law of thermal equilibrium. Gel time, gel temperature, and glass transition temperature are detected by linear fitting and differential analysis of the strain variation with temperature inside the sample based on the thermal expansion coefficient. Differential scanning calorimetry and SB(m, n) autocatalytic reaction model are used to calculate the curing kinetic equation and to comparatively verify the glass transition temperature and curing degree. The differences between the two test results of the glass transition temperature, curing initiation time, and curing completion time are 0.39 %, 11.2 %, and 17.6 %, respectively. The proposed method can be used for detecting and evaluating the processes and formulations of GIS insulators in the same batch of production samples and optimizing the processes and formulations.